2018
DOI: 10.1159/000486802
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Risk Assessment in Upper Gastrointestinal Bleeding: Comparison of 5 Scores Predicting 7 Outcomes

Abstract: Introduction: Although different scores have been suggested to predict outcomes in the setting of upper gastrointestinal bleeding (UGIB), few comparative studies between simplified versions of older scores and recent scores have been published. We aimed to evaluate the accuracy of pre- (PreRS) and postendoscopic Rockall scores (PostRS), the Glasgow-Blatchford score (GBS) and its simplified version (sGBS), as well as the AIMS65 score in predicting different clinical outcomes. Methods: In this retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…[ 22 ] A study of 433 UGIB patients found that AIMS65 was inferior to GBS at predicting rebleeding. [ 29 ] In our study, although the four risk scores are effective in predicting rebleeding, it is consistent with the results of most previous studies, that is, the AUROCs of 4 scores are all less than 0.7. It may indicate that it is difficult to directly predict and evaluate whether rebleeding will occur in UGIB people through vital signs or biochemical indicators at admission.…”
Section: Discussionsupporting
confidence: 92%
“…[ 22 ] A study of 433 UGIB patients found that AIMS65 was inferior to GBS at predicting rebleeding. [ 29 ] In our study, although the four risk scores are effective in predicting rebleeding, it is consistent with the results of most previous studies, that is, the AUROCs of 4 scores are all less than 0.7. It may indicate that it is difficult to directly predict and evaluate whether rebleeding will occur in UGIB people through vital signs or biochemical indicators at admission.…”
Section: Discussionsupporting
confidence: 92%
“…In our study population, none of the scores were predictive of prolonged hospital stay of >3 days which was similar to another study (21) . GBS was the best in predicting the need for blood transfusion as seen by Robertson et al and Goncalves et al (21,27) . The cut-off score for the need for blood transfusion was found ≥10 which was consistent with Robertson et al (21) .…”
Section: Discussionmentioning
confidence: 83%
“…GBS and AIMS65 were also fairly predictive for need intensive care unit admission with cut off at 12 and 2 respectively. AIMS65 followed by MEWS were predictive for the need for surgical intervention at a cutoff score of ≥3 and ≥4 respectively whereas Goncalves et al have reported GBS as the only score predictive for surgical intervention (27) . However, patients undergoing surgical intervention were very few (only two); hence predictive ability may not be clinically acceptable.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…La AIMS65 destaca sobre las otras escalas debido a que presenta una menor complejidad, lo que le permite ser más usada en la práctica clínica diaria 57 . 61,62 .…”
Section: Discusión Sobre Las Escalas De Evaluaciónunclassified